Rancang Bangun Aplikasi Manajemen Data Stok Barang Untuk Industri Kuliner Multi-Branch - Yogga Herlambang, Helwy; Ayumi, Vina (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
Technological advancements have also led to the creation of web applications for the promotion of culinary and online services, increasing the visibility and accessibility of culinary businesses. Stock applications are essential for maintaining operations, managing resources, and adapting to market demands in the culinary business. The purpose of this study is to develop and implement a stock management system for PT. ABC specifically aims to improve the accuracy of stock data, facilitate inventory tracking, increase transparency in stock management and implement a system that can be accessed online and in real-time. This research was conducted in the period from April to July 2024. Data collection was carried out by conducting literature studies, observations and interviews conducted with the general manager and administrator of the logistics division). Based on the results of the research, the stock data management application for the multi-branch culinary industry consists of a login menu, a master menu, a transaction & invoice menu, a report menu and a settings menu. The login page is used to log in to the dashboard, using a username and password. The master menu page consists of several sub-menus, namely: Products & Stock, Product Categories, Suppliers, and Customers & Divisions. The Transactions & Invoices menu page consists of several sub-menus, namely: all orders and invoices.